From the personal to the academic: Autoethnography as an essential tool for researching the effect of migration processes on migrant women's identities - Macías-Gómez-Estern, Beatriz; Tarazona-Ochoa, Vibian Andrea (Comparative Cultural Studies: European and Latin American Perspectives, 2024)
The article analyses the advantages and convenience of using autoethnographic methodology in researching the impact of migration processes on migrant women's identities. It compares autoethnography with other qualitative and quantitative methods, highlighting autoethnography's ability to capture personal and subjective experiences, empower the researcher and encourage reflexivity. Autoethnographic methodology is contrasted with phenomenology, ethnography, grounded theory, narrative analysis and quantitative methods, with concrete examples of each approach. Previous studies using autoethnography in similar contexts are presented and a research design specific to the phenomenon under study is proposed, addressing methodological justifications, challenges and ethical considerations. The analysis shows that autoethnography is an essential and highly interesting tool for understanding the complexity of migrant identity from a gendered and decolonial perspective.